Geodynamic significance of preserved Carboniferous subduction complex in Atbashi range (South Tianshan, Kyrgyzstan) and inferences for crustal-scale structure of north Tarim-Tibet orogenic system (Journal of Nepal Geological Society, 2013)
A subduction complex of carboniferous age is preserved in the South Tianshan belt of Kyrgyzstan. It is made of a LP-LT accretionnary prism comprising an obducted ophiolite thrusted by a HP complex made of a sedimentary channel including eclogites boudins and a continental unit. Its structure and metamorphic history are investigated to reconstruct the geodynamic evolution of the northern Tarim in the Upper Palaeozoic. This study gives insights into the crustal-scale structure of this mountain belt, currently intensely reactivated by the India-Asia collision. Eclogites boudins have a N-MORB type composition similar to the unmetamorphosed obducted ophiolite sequence. Evidence for eclogite facies in both acidic and mafic lithologiesand geological structure are in agreement with a deep subduction channel mainly comprised of metasediments. Eclogites boudins are investigated for a preliminary PT study. Prograde stage (I) begins in blue-schist/eclogite facies transition at 520 ± 30°C - 17 ± 1 kbar. Condit ions of peak metamorphism (II) in eclogite facies range from 550 ± 30°C - 18.5 ± 1 kbar to 540- 595°C - 21 kbar. Retrograde stage (III) is also in the eclogite facies conditions at 515 ± 30°C - 16.7 ± 1 kbar. The geological structure and metamorphic conditions of this suture zone implies the subduction of a narrow oceanic basin in a south-dipping subduction zone, while another north-dipping subduction was active below Middle Tianshan. Final stacking of Middle and South Tianshan occurred at 320-310 Ma. These antithetic subduction zones are still reflected in the main structures of Tianshan. Reactivation of the south dipping structures since 30 Ma is ascribed to explain the current localisation of uplift and deformation.